2008
DOI: 10.1364/oe.16.018844
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond polarized supercontinuum generation controlled by intermodal four-wave mixing for fluorescence lifetime imaging microscopy

Abstract: We present the generation of a picosecond polarized supercontinuum in highly birefringent multimodal microstructured fiber. The initial steps of the spectral broadening are dominated by intermodal four-wave mixing controlled by the specific fiber design. Using a low repetition rate ultra-stable solid state laser, a pulse train well-suited for versatile time-domain fluorescence lifetime imaging applications is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…By adjusting the geometrical parameters of a PCF, primarily including the core diameter, the air-hole diameter and the hole pitch, the dispersion properties, especially the zerodispersion wavelength (ZDW), can be designed to meet the phase-matching requirements, facilitating the realization of a broad SC spectrum [9][10][11][12][13][14][15] . The UV to near-IR region is important in biomedical imaging and fluorescence lifetime imaging fields [16,17] . However, these applications always require a linearly polarized SC, whereas the generated SC is generally unpolarized.…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the geometrical parameters of a PCF, primarily including the core diameter, the air-hole diameter and the hole pitch, the dispersion properties, especially the zerodispersion wavelength (ZDW), can be designed to meet the phase-matching requirements, facilitating the realization of a broad SC spectrum [9][10][11][12][13][14][15] . The UV to near-IR region is important in biomedical imaging and fluorescence lifetime imaging fields [16,17] . However, these applications always require a linearly polarized SC, whereas the generated SC is generally unpolarized.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have experimentally demonstrated the generation of broadband supercontinua in nonlinear PCF that broadly agree with the numerical simulations of the generalized nonlinear Schrödinger equation (GNLSE) [4,5], which is the differential equation describing spatio-temporal pulse evolution resulting from Maxwell's equations inside an optical fibre. The majority of these studies have demonstrated unpolarized SC spectra, but many applications require polarized SC spectra from birefringent fibres [6,7]. Advantages of using birefringent fibre include the fact that all the spectral components exhibit the same stable linear polarization and a reduced power requirement for SC generation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, self-phase modulation (SPM) and soliton effects dominate SC generation for sub-picosecond pump pulses, while four-wave mixing (FWM) and stimulated Raman scattering (SRS) contribute to spectral broadening for tens of picosecond pump pulses. 7,8 Long picosecond laser pulses could facilitate cost-effective SC generation. 9 With high-power picosecond pump pulses generated from fiberbased master oscillator power amplifiers, high-power SC light sources could reach tens of watts, which were typically realized in large-mode-area PCFs of sufficient lengths up to a few tens of meters.…”
mentioning
confidence: 99%